Urban and Rural Area Graduate Students’ Perceptions toward Synchronous English Learning amidst Covid-19 Pandemic - Puteri Anugrah Septianingsih; Setia Erliza (Yayasan Visi Intan Permata, 2021)
Teachers and students are forced to change the learning system from face-to-face into virtual learning through synchronous and asynchronous. This transformation perhaps raises various perceptions both urban and rural area students since they have sundry backgrounds and conditions. Therefore, this study aims to investigate the EFL urban and rural area graduate students’ perceptions towards synchronous learning amidst covid-19 pandemic. The respondents of this study were 30 EFL graduate students at English Department in State University of Malang, including 17 urban area students and 13 rural area students who were from 1st semester and 3rd semester. This study was conducted by using survey research design. Furthermore, the data of this study were collected by distributing questionnaire in the form of Google Forms with the combination of close and open ended questions. The findings were urban and rural area students had no significantly different perceptions towards synchronous learning. There were only some different perceptions in terms of learning motivation, learning style, and suitability of the course goal. In addition, the urban and rural area students perceive positive responses to synchronous learning, then synchronous learning can be classified as the effective online learning during this pandemic. However, their common problem was from the slow-speed internet connection. Thus, they feel that synchronous learning is not as effective as face to face learning.